2005
DOI: 10.2741/1551
|View full text |Cite
|
Sign up to set email alerts
|

Brain chemotherapy from the bench to the clinic: targeting neuronal survival with small molecule inhibitors of apoptosis

Abstract: Increasing evidence implicates aberrant apoptosis as a fundamental cause of neurodegenerative diseases. Thus elucidating the underlying causes of neuronal programmed cell death may foster the development of therapeutic interventions. Research in the last 15 years provided a solid foundation for understanding molecular mechanisms of neuronal apoptosis. This review discusses the major molecules and signaling pathways leading to neuronal survival or apoptosis with emphasis on several small molecule inhibitors tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 166 publications
0
3
0
Order By: Relevance
“…The opposing effects of cAMP-mediated signalling on the survival of specific lymphoid and myeloid cell subsets remains thus far largely unexplained. However, it should be noted that, while cAMP promotes apoptosis within lymphoid subsets, as well as some other cell types, including lung and mammary carcinoma cells [34], ovarian granulosa cells [217], fibroblasts [218] and primary cultured cardiomyocytes [219], a considerably wider range of cell lineages, including myeloid cells, pancreatic β-cells, hepatocytes, gastric and intestinal epithelial cells, and spinal motor, superior cervical ganglion sympathetic, dorsal root sensory, dopaminergic, cerebellar granule and septal cholinergic neurons, have been described in which cAMP signalling is antiapoptotic [220][221][222][223][224]. Whether cAMP-mediated signalling will be pro-or anti-apoptotic, however, appears to depend on a number of different factors, including the nature of the stimulus, the nature of the cAMP effectors that predominate in the cell, the particular locale in which the cAMP signal occurs, and the strength of the signal.…”
Section: Aml (Acute Myeloid Leukaemia) and The Role Of Camp In Myeloimentioning
confidence: 99%
“…The opposing effects of cAMP-mediated signalling on the survival of specific lymphoid and myeloid cell subsets remains thus far largely unexplained. However, it should be noted that, while cAMP promotes apoptosis within lymphoid subsets, as well as some other cell types, including lung and mammary carcinoma cells [34], ovarian granulosa cells [217], fibroblasts [218] and primary cultured cardiomyocytes [219], a considerably wider range of cell lineages, including myeloid cells, pancreatic β-cells, hepatocytes, gastric and intestinal epithelial cells, and spinal motor, superior cervical ganglion sympathetic, dorsal root sensory, dopaminergic, cerebellar granule and septal cholinergic neurons, have been described in which cAMP signalling is antiapoptotic [220][221][222][223][224]. Whether cAMP-mediated signalling will be pro-or anti-apoptotic, however, appears to depend on a number of different factors, including the nature of the stimulus, the nature of the cAMP effectors that predominate in the cell, the particular locale in which the cAMP signal occurs, and the strength of the signal.…”
Section: Aml (Acute Myeloid Leukaemia) and The Role Of Camp In Myeloimentioning
confidence: 99%
“…This research has identified many compounds including antibiotics, antioxidants, anti-inflammatory agents, neurotransmitter receptor agonists, cytokine inhibitors, apoptosis blockers, and growth factors that protect and preserve the hair cells, neurons, and supporting cells of the cochlea (Breuskin et al, 2008;Crumling and Raphael, 2006;Darlington and Smith, 2007;Fritzsch et al, 2006;Gillespie and Shepherd, 2005;Guitton et al, 2004;Holley, 2002;Lalwani et al, 2002;Patel et al, 2004;Pettingill et al, 2007;Raphael, 2002;Richardson et al, 2006;Rybak and Somani, 1999;Rybak and Whitworth, 2005;Seidman and Van De Water, 2003;Seidman and Vivek, 2004;Tang et al, 2006;Weber, 2002). Similar research on the central nervous system has yielded compounds including anti-apoptotic agents, amino acids, neurotransmitter receptor agonists, antioxidants, anti-inflammatory agents, calcium, hormones, and growth factors which are useful in promoting the survival of neurons in many traumatic and neurodegenerative states (Chin and D'Mello, 2005;Diem et al, 2007;Friedman, 2006;Hara, 2007;Hoffman et al, 2006;Lescot et al, 2006;Sweeney, 1997). Cell delivery, gene therapy, and tissue engineering approaches to repairing traumatic injury and diseases of the brain and central nervous system have also produced promising results for the regeneration of lost neurons (Buch et al, 2007;Mochizuki, 2007;Shen et al, 2007).…”
Section: Pharmaceuticals For Improved Auditory Prosthesis Therapymentioning
confidence: 95%
“…The first theory proposes that elevation of intracellular cAMP is beneficial for suppressing cell proliferation in most mesenchymal and epithelial cell lines, such as glioblastoma (Kang et al 2014), thyroid cells (Sawa et al 2017), lung and breast carcinoma cells (Lerner and Epstein 2006), ovarian granulosa cells (Zwain and Amato 2001), fibroblasts (Huston et al 2006), and primary cardiomyocytes (Ding et al 2005). In contrast, the second theory proposes that cAMP promotes cell survival, which has been observed in myeloid cells, pancreatic -cells, hepatocytes, gastric and intestinal cells, spinal motor, superior cervical ganglion sympathetic, dorsal root ganglion, dopaminergic neurons, cerebral granule and septal cholinergic neurons (Kwon et al 2004, Lerner and Epstein 2006, Cullen et al 2004, Nishihara et al 2003, Hoshino et al 2003, Chin and D'Mello 2005. These two divergent roles of cAMP may be crucial in both physiological maintenance and pathological conditions, but whether these signalling cascades are interconnected remains unclear.…”
Section: Introductionmentioning
confidence: 99%